Actualización diagnóstica y terapéutica de la esclerodermia localizada - Silva Alcívar, Gabriela Alejandra (2023)
ABSTRACT: Scleroderma is an autoimmune disease that has several clinical forms of presentation. Localized and systemic involvement characterized by the presence of extra- cutaneous manifestations is described. Localized scleroderma tends to occur more frequently in children, and may evolve into systemic scleroderma in the future. The importance of early diagnosis focuses on the delay in the appearance of complications or evolution towards the systemic form. The objective of this research was to carry out a bibliographic review to update the knowledge related to the diagnostic and therapeutic management of localized scleroderma. For this, a basic, descriptive and cross-sectional investigation was carried out consisting of a bibliographic review of documents published in the last 5 years. A total of 81 documents were identified, of which 36 were used in the study. The information was obtained from regional (Latindex, Lilacs, Scielo, and Redalyc) and high-impact databases (Scopus, Medline, PubMed, and Ice Web of Science). The main results include the description of the elements that enable the clinical suspicion of the disease to be activated and, subsequently, its definitive diagnosis to be confirmed. These elements were based on the clinical, epidemiological, diagnostic and therapeutic characteristics of the disease. The main pharmacological groups and drugs to be used based on their pharmacological characteristics were also described. It is concluded that the diagnosis of localized scleroderma can be difficult and that it must be confirmed with histopathological studies. Keywords: Rheumatic disease; Sclerodactyly; scleroderma; Raynaud's phenomenon; SAPHO syndrome